Bis(tetraphenylarsonium) hexafluoridotechnetate(IV) dihydrate: preparation, structure and spectroscopic analysis. Issue 12 (14th November 2019) - Balasekaran, Samundeeswari Mariappan; Poineau, Frederic
Abstract : The salt bis(tetraphenylarsonium) hexafluoridotechnetate(IV) dihydrate, (AsPh4 )2 [TcF6 ]·2H2 O, was prepared for the first time from a cation metathesis reaction of (NH4 )2 [TcF6 ] in water. Abstract : Reports of quadrivalent transition‐metal fluoride salts containing bulky organic cations are limited. In this context, we prepared the bis(tetraphenylarsonium) hexafluoridotechnetate(IV) dihydrate salt, (C24 H20 As)2 [TcF6 ]·2H2 O, by a cation metathesis reaction of (NH4 )2 [TcF6 ] in water. This is the first report of an arsonium salt of the hexafluoridotechnetate(IV) dianion. (AsPh4 )2 [TcF6 ]·2H2 O crystallizes in the triclinic space group P . The [TcF6 ] 2− anion adopts a slightly distorted octahedral geometry with an average Tc—F bond length of 1.933 Å. The cyclic voltammogram of (AsPh4 )2 [TcF6 ]·2H2 O in CH3 CN shows a one‐electron reversible oxidation wave at 1.496 V.